Aberrant Splicing Induced by Dysregulated Rbfox2 Produces Enhanced Function of CaV1.2 Calcium Channel and Vascular Myogenic Tone in Hypertension. Issue 6 (December 2017) - Zhou, Yingying; Fan, Jia; Zhu, Huayuan; Ji, Li; Fan, Wenyong; Kapoor, Isha; Wang, Yue; Wang, Yuan; Zhu, Guoqing; Wang, Juejin
Abstract : Calcium influx from activated voltage-gated calcium channel CaV 1.2 in vascular smooth muscle cells is indispensable for maintaining myogenic tone and blood pressure. The function of CaV 1.2 channel can be optimized by alternative splicing, one of post-transcriptional modification mechanisms. The splicing factor Rbfox2 is known to regulate the CaV 1.2 pre-mRNA alternative splicing events during neuronal development. However, Rbfox2's roles in modulating the key function of vascular CaV 1.2 channel and in the pathogenesis of hypertension remain elusive. Here, we report that the proportion of CaV 1.2 channels with alternative exon 9* is increased by 10.3%, whereas that with alternative exon 33 is decreased by 10.5% in hypertensive arteries. Surprisingly, the expression level of Rbfox2 is increased ≈3-folds, presumably because of the upregulation of a dominant-negative isoform of Rbfox2. In vascular smooth muscle cells, we find that knockdown of Rbfox2 dynamically increases alternative exon 9*, whereas decreases exon 33 inclusion of CaV 1.2 channels. By patch-clamp studies, we show that diminished Rbfox2-induced alternative splicing shifts the steady-state activation and inactivation curves of vascular CaV 1.2 calcium channel to hyperpolarization, which makes the window current potential to more negative. Moreover, siRNA-mediated knockdown of Rbfox2 increases the pressure-induced vascular myogenic tone of rat mesenteric artery. Taken together, our data indicate that Rbfox2 modulates the functions of vascular CaV 1.2 calcium channel by dynamically regulating the expressions of alternative exons 9* and 33, which in turn affects the vascular myogenic tone. Therefore, our work suggests a key role for Rbfox2 in hypertension, which provides a rational basis for designing antihypertensive therapies. Abstract : Supplemental Digital Content is available in the text.